Estudo sobre o nível de letramento em saúde dos portadores de doença renal crônica submetidos à terapia renal substitutiva - Rocha, Késia Tomasi da (2018)
Objective: To study the impact of the level of health literacy in patients submitted to hemodialysis, peritoneal dialysis and renal transplantation, regarding cognitive aspects, drug compliance and quality of life. Method: Cross-sectional study, performed with individuals over 18 years of age, who underwent some type of renal replacement therapy for more than three months. The Brazilian versions of the instruments were used: Short Assessment of Health Literacy for Portuguese-speaking Adults-18 (SAHLPA-18), Mini Mental State Examination (MMSE), 36-Item Short Form (SF-36) and Morisky scale, as well as a questionnaire on clinical and sociodemographic data. Results: 138 patients were evaluated, 50 (36.2) undergoing hemodialysis, 23 (16.7%) undergoing peritoneal dialysis and 65 (47.1%) undergoing renal transplantation. The mean age was 52.0 ± 15.5 years and 58.0% male. Patients with inadequate literacy (51.4%) had income equal to or less than a minimum wage (P=0.002), complete or lower primary education (P <0.001) and moderate cognitive decline (P=0.003). Individuals with adequate health literacy had incomplete high school education or higher education, income equal to or greater than five minimum wages and higher score in the emotional aspects of quality of life (P=0.052). Conclusions: our results suggest that the level of health literacy is associated with lower income, schooling and cognitive deficits in patients submitted to renal function replacement.